Why life gets better after age 50, for some: mental well-being and the social norm of work - Coen van de Kraats; Titus Galama; Maarten Lindeboom (Tinbergen Institute, 2022)
We provide evidence that the social norm (expectation) of work has a detrimental causal effect on the mental well-being of individuals not able to abide by it. Using SHARE data on men aged 50+ from 10 European countries, we identify the social norm of work effect in a difference-in-differences (DiD) model that compares mental well-being scores of unemployed / disabled individuals (the treatment group) with those of employed / retired individuals (the control group) at varying levels of the fraction of retirees of comparable age. The initial mental well-being gap at age 50 is large, with unemployed / disabled men experiencing lower levels of mental well-being. Beyond age 50, the mental well-being of unemployed and disabled men improves as peers of comparable age retire, and full convergence occurs generally at an age that is slightly above the normal retirement age, when everyone has retired. We estimate the social norm of work effect to be comparable to the benefit of tertiary education, the detriment of being widowed, and the benefit of having a household income of 2,000,000 Euros. We explore income-security and leisure-coordination channels as alternative interpretations of the effect to show that these cannot explain our findings.
Keywords: I10; I31; J60; D63; 330; mental well-being; social norm of work; retirement institutions